2021
DOI: 10.1007/s40333-021-0112-3
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of carbon exchange in global drylands

Abstract: Drylands refer to regions with an aridity index lower than 0.65, and billions of people depend on services provided by the critically important ecosystems in these areas. How ecosystem carbon exchange in global drylands (CED) occurs and how climate change affects CED are critical to the global carbon cycle. Here, we performed a comprehensive bibliometric study on the fields of annual publications, marked journals, marked institutions, marked countries, popular keywords, and their temporal evolution to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The results also revealed that the publications number improved very slightly from 1991-2006 with around 15 papers each year, while they dramatically increased during 2015-2022 ( Figure 5 ) with 80% of publications found after 2005. The trend of root plasticity during both drought and recovery research was consistent with the trend in the related emerging topic of “carbon exchange in global drylands” ( Liu et al., 2021 ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The results also revealed that the publications number improved very slightly from 1991-2006 with around 15 papers each year, while they dramatically increased during 2015-2022 ( Figure 5 ) with 80% of publications found after 2005. The trend of root plasticity during both drought and recovery research was consistent with the trend in the related emerging topic of “carbon exchange in global drylands” ( Liu et al., 2021 ).…”
Section: Resultssupporting
confidence: 80%
“…The thematic analysis distinguishes “motor” from “basic” themes. Motor themes are both important, well-developed, and highly cited in recent years, whereas basic themes are the main and driving keywords for the research topic but receive a few citations ( Cobo et al., 2011 ; Liu et al., 2021 ). To the motor themes belonged words like “water stress”, “stomatal conductance”, “abscisic-acid”, “chlorophyll fluorescence”, “biomass”, “proline”, and “hydraulic conductivity” whereas “drought”, “recovery”, “photosynthesis”, “root”, “climate change”, “growth” and “resilience” were the basic themes ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The number of publications can reflect the popularity, advancements, and significance of research in the field of SP [29,30]. The overall trend in literature showed a consistent growth in the volume of published works from 1991 to 2021, with a rapid increase from 2001 to 2021 (Figure 1a).…”
Section: Temporal Patterns In the Publication And Citation Landscapementioning
confidence: 93%
“…Bibliometric analysis is a statistical method that uses modern technologies, such as computer engineering, database management and statistics, to quantitatively evaluate articles, books and any other publications. It has been applied in a lot of fields of study [ 27 , 28 , 29 ]. Although bibliometrics are quantitative in nature, these methods are also used to illustrate qualitative features.…”
Section: Data Analysis and Methodsmentioning
confidence: 99%
“…Research trends and frontiers can be well reflected by frequently used keywords [ 27 ]. Wordcloud can quickly present the most important words and locate different words in alphabetical order to determine their relative importance in related fields.…”
Section: Data Analysis and Methodsmentioning
confidence: 99%